Romance in “Christabel”: Fear of the Supernatural Other - Seibel, Jamie; Cope, Jonas (Journal of Student Research, 2023)
Literary romance is a difficult term to coherently define among critics. Dating back to the thirteenth century in Middle English, the number of romances written in the preceding English centuries offers an expansive opportunity for scholarly research and debate. One commonality that may be examined is the presence of a hero/heroine and a supernatural entity meant to challenge the protagonist’s inability to live up to ideals. Spanning from 1785 to 1832, British Romanticism is a movement that critics also have trouble defining. Literature written during the Romantic period includes the first and second-generation poets, who were present during and after the French Revolution respectively. The selected Romantic-era poem of study is “Christabel” by Samuel Taylor Coleridge due to its presence of a heroine in Christabel and a supernatural entity in Geraldine. When placing literary romance’s Morgan le Fay and Geraldine in juxtaposition with one another, a clearer definition of romance and Romanticism may be formed. “Christabel” invokes literary romance’s tendency to depict a supernatural other who is not inherently evil but complicates through sexual temptation the hero’s struggle with chastity. The supernatural other is someone who is outcasted and alienated from society because they are a perceived threat to normalcy. However, Sir Gawain and the Green Knight, Le Morte Darthur, and “Christabel” demonstrate how the real threat is often the hero/heroine’s inability to deny temptation. This research ultimately reveals how the hero and supernatural other become vehicles to reflect common weaknesses and flaws that make people human.